A qualitative formative evaluation of a patient facing intervention to improve care transitions for older people moving from hospital to home. (3rd September 2022) - Shannon, Rosie; Baxter, Ruth; Hardicre, Natasha; Mills, Thomas; Murray, Jenni; Lawton, Rebecca; O'Hara, Jane K.
Abstract: Background: The Partners at Care Transitions (PACTs) intervention was developed to support older people's involvement in hospital to improve outcomes at home. A booklet, question card, record sheet, induction leaflet,  and patient‐friendly discharge letter support patients to be more involved in their health and wellbeing, medications, activities of daily living and post‐discharge care. We aimed to assess intervention acceptability, identify implementation tools, and further develop the intervention. Methods: This was a qualitative formative evaluation involving three wards from one hospital. We recruited 25 patients aged 75 years and older. Ward staff supported intervention delivery. Data were collected in wards and patients' homes, through semi‐structured interviews, observation,  and documentary analysis. Data were analysed inductively and iteratively with findings sorted according to the research aims. Results: Patients and staff felt there was a need for, and understood the purpose of, the PACT intervention. Most patients read the booklet but other components were variably used. Implementation challenges included time, awareness,  and balancing intervention benefits against risks. Changes to the intervention and implementation included clarifying the booklet's messages, simplifying the discharge letter to reduce staff burden,  and using prompts and handouts to promote awareness. Conclusion: The PACT intervention offers a promising new way to improve care transitions for older people by supporting patient involvement in their care. After further development of the intervention and implementation package, it will undergo further testing. Patient or Public Contribution: This study regularly consulted a panel representing the local patient community, who supported the development of this intervention and its implementation.